Effortful Control in “Hot” and “Cool” Tasks Differentially Predicts Children’s Behavior Problems and Academic Performance - Kim, Sanghag (2013)
Effortful control (EC), the capacity to deliberately suppress a dominant response and perform a subdominant response, rapidly developing in toddler and preschool age, has been shown to be a robust predictor of children’s adjustment. Not settled, however, is whether a view of EC as a heterogeneous rather than unidimensional construct may offer advantages in the context of predicting diverse developmental outcomes. This study focused on the potential distinction between “hot” EC function (delay-of-gratification tasks that called for suppressing an emotionally charged response) and more abstract “cool” EC functions (motor inhibition tasks, suppressing-initiating response or Go-No Go tasks, and effortful attention or Stroop-like tasks). Children (N=100) were observed performing EC tasks at 38 and 52 months. Mothers, fathers, and teachers rated children’s behavior problems and academic performance at 67, 80, and 100 months, and children participated in a clinical interview at 100 months. Structural Equation Modeling (SEM) analyses with latent variables produced consistent findings across all informants: Children’s scores in “hot” EC tasks, presumably engaging emotion regulation skills, predicted behavior problems but not academic performance, whereas their scores in “cool” EC tasks, specifically those engaging effortful attention, predicted academic performance but not behavior problems. The models of EC as a heterogeneous construct offered some advantages over the unidimensional models. Methodological and clinical implications of the findings are discussed.